(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2024)
This article talks about soil formation, genesis, the study of soils, the work of researchers, as well as the ecological state of the soil in the Aravan and Kara-Suu regions of Southern Kyrgyzstan, the influence of anthropogenic processes on the soil and methods of combating it. solve it, research methods are provided.